The predictive value of serum ox-LDL and 25-(OH)-D levels for cerebral edema in patients with hypertensive cerebral hemorrhage: serum ox-LDL and 25-(OH)-D levels for cerebral edema in hypertensive cerebral hemorrhage - Xu, Chao; Wang, Bo; Liu, Niu; Bao, Lei (Journal of Medical Biochemistry, 2025)
[Objective] To analyze the predictive value of serum oxidation-modified low-density lipoprotein (ox-LDL) and 25-hydroxyvitamin D[25-(OH)-D] levels before minimally invasive hematoma evacuation in patients with hypertensive intracerebral hemorrhage (HICH) for cerebral edema. [Methods] 300 patients with HICH in our hospital from August 2022 to August 2024 were selected as research subjects. Patients were divided into a high-level ox-LDL group (ox-LDL≥50 μg/dL) and a low-level ox-LDL group (ox-LDL<50 μg/dL) according to their preoperative serum ox-LDL level. The patients were separated into two groups based on the amount of serum 25-(OH)-D: high-level 25-(OH)-D (25-(OH)-D≥30 ng/mL) and low-level 25-(OH)-D (25-(OH)-D<30 ng/mL). The incidence of cerebral edema within 48 hours after surgery was compared among the groups. Following minimally invasive hematoma evacuation in patients with HICH, the predictive value of preoperative serum ox-LDL and 25-(OH)-D levels for cerebral edema was evaluated using the receiver operating characteristic (ROC) curve. [Results] The hematoma volume varied in statistically meaningful ways, fibrinogen level and incidence of cerebral edema among patients with different serum ox-LDL and 25-(OH)-D levels (P<0.05). The results of point–bisenteric correlation analysis revealed that the occurrence of cerebral edema in HICH patients was positively correlated with the serum ox-LDL level (r=0.455, P<0.05) and negatively correlated with the serum 25-(OH)-D level (r=-0.534, P<0.05). Pearson correlation analysis revealed that there was a negative correlation between the serum ox-LDL level and the 25-(OH)-D level (r=-0.444, P<0.05). The areas under the curve (AUCs) of preoperative serum ox-LDL, 25-(OH)-D alone, and combined detection for predicting cerebral edema following minimally invasive hematoma evacuation in patients with HICH were 0.777, 0.768, and 0.839, respectively, according to the results of the ROC curve analysis. The AUC of combined detection was the largest. [Conclusion] Before minimally invasive hematoma evacuation in patients with HICH, the serum ox-LDL level was high, and the 25-(OH)-D level was low. Preoperative serum ox-LDL and 25-(OH)-D levels have high predictive value for cerebral edema after minimally invasive hematoma evacuation in patients with HICH.